Inquiry Social Complexity-Based Chemistry Module to Empower Critical and Creative Thinking Skills - Perdana, Ryzal; Wahyudin, Yasser (FKIP Universitas Lampung, 2022)
The Validity of the Chemistry Module Based on Inquiry Social Complexity (ISC) to Empower Critical and Creative Thinking (CCT) Skills. A study has been conducted on the validity of the inquiry social complexity (ISC) based learning module to empower students' critical and creative thinking skills. The research method uses descriptive methods. The learning modules developed are validated and evaluated. Validation is carried out for experts in the fields of language, material, design, and learning instruments. While the evaluation phase is given to teachers and students, this is because teachers and students are directly involved in the implementation of the ISC module. So it is expected that the ISC module evaluation results can be objective. ISC module evaluation given to teachers and students consists of four aspects, namely Content, Language, Presentation, and Graphic. The assessment criteria consist of a scale of 4, while the assessment by experts and evaluators uses a Likert 4 scale. The results of the language expert assessment, material, design, and evaluation of learning are in the excellent category. Student assessment results are in the very good category, and teacher ratings are in a good category. Keywords: inquiry social complexity (isc), modules, critical thinking, creative thinking, chemistry.